1979
DOI: 10.1002/jsfa.2740300317
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and differentiation of grape brandies by multiple discriminant analysis

Abstract: Gas chromatography has shown that clear, quantitative differences exist between the various flavour constituents of German and French grape brandies as well as French cognacs. The amounts of some selected flavour compounds from 24 grape brandies have been submitted to multiple discriminant analysis. Discriminant analysis was carried out in three parts corresponding to the column chromatographic pre‐separation of volatile compounds into three fractions (I: non‐polar compounds; II: oxo compounds; III: hydrophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
5

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 4 publications
0
13
0
5
Order By: Relevance
“…Jounela--Eriksson 11 reported that if ethyl esters were added or removed from the spirits, a negative effect on the overall odour intensity resulted. Postel and Adam 12 and Schreier et al 13 also showed that ethyl esters could be used to analytically differentiate between cognacs and other groups of grape brandies.…”
Section: Resultsmentioning
confidence: 96%
“…Jounela--Eriksson 11 reported that if ethyl esters were added or removed from the spirits, a negative effect on the overall odour intensity resulted. Postel and Adam 12 and Schreier et al 13 also showed that ethyl esters could be used to analytically differentiate between cognacs and other groups of grape brandies.…”
Section: Resultsmentioning
confidence: 96%
“…These techniques have been reported to be useful for establishing the identity of unknown-grape-derived samples (Schreirer and Reiner 1979 …”
Section: Introductionmentioning
confidence: 98%
“…Major and minor volatile components have been used by several authors in the characterization of alcoholic beverages (Schreier and Reiner 1979;Lehtonen 1983;Battaglia 1986;Pino et al 1994). Multivariate statistical techniques have also been used to establish the identity of unknown samples (Lisle et al 1978;Martin et af.…”
Section: Introductionmentioning
confidence: 99%